Bone Mineral Density Changes Among Women Initiating Proton Pump Inhibitors or H2 Receptor Antagonists: A SWAN Cohort Study. (February 2015) - Solomon, Daniel H; Diem, Susan J; Ruppert, Kristine; Lian, Yin Juan; Liu, Chih‐Chin; Wohlfart, Alyssa; Greendale, Gail A; Finkelstein, Joel S
ABSTRACT Proton pump inhibitors (PPIs) have been associated with diminished bone mineral density (BMD) and an increased risk of fracture; however, prior studies have not yielded consistent results, and many have suboptimal ascertainment of both PPI use and BMD. We used data from the Study of Women's Health Across the Nation (SWAN), a multicenter, multi‐ethnic, community‐based longitudinal cohort study of women across the menopause transition to examine the association between annualized BMD changes and new use of PPIs. We compared changes in BMD in new PPI users with changes in BMD in new users of histamine 2 receptor antagonists (H2RAs) and with changes in BMD in subjects who did not use either class of medications. Mixed linear regression models included recognized risk factors for osteoporosis, including demographics, menopausal transition stage, body mass index (BMI), lifestyle factors, as well as comorbidities and concomitant medications. To provide further evidence for the validity of our analytic approach, we also examined the effects of hormone‐replacement therapy (HT), a class of medications that should reduce bone loss, on changes in BMD as an internal positive control group. We identified 207 new users of PPIs, 185 new users of H2RAs, and 1, 676 non‐users. Study subjects had a mean age of 50 years and were followed for a median of 9.9 years. Adjusted models found no difference in the annualized BMD change at the lumbar spine, femoral neck, or total hip in PPI users compared with H2RA users or non‐users. These results were robust to sensitivity analyses. BMD increased as expected in HT users, supporting the validity of our study design. These longitudinal analyses plus similar prior studies argue against an association between PPI use and BMD loss. © 2014 American Society for Bone and Mineral Research.